2017
DOI: 10.1088/1748-9326/aa7f10
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis of funding and focus in US advanced fission innovation

Abstract: Deep decarbonization of the global energy system will require large investments in energy innovation and the deployment of new technologies. While many studies have focused on the expenditure that will be needed, here we focus on how government has spent public sector resources on innovation for a key carbon-free technology: advanced nuclear. We focus on nuclear power because it has been contributing almost 20% of total US electric generation, and because the US program in this area has historically been the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 13 publications
(26 reference statements)
0
9
0
Order By: Relevance
“…Our analysis suggests that in order for advanced nuclear technologies to play a role in deep decarbonization over the next several decades, more competent stewardship of nuclear innovation, substantially greater appropriations, and a change in energy markets, all very heavy lifts, will be required (23,24).…”
Section: Advanced Us Designs Will Not Be Available For Many Decadesmentioning
confidence: 99%
See 3 more Smart Citations
“…Our analysis suggests that in order for advanced nuclear technologies to play a role in deep decarbonization over the next several decades, more competent stewardship of nuclear innovation, substantially greater appropriations, and a change in energy markets, all very heavy lifts, will be required (23,24).…”
Section: Advanced Us Designs Will Not Be Available For Many Decadesmentioning
confidence: 99%
“…In fact, its current vision is for at least two of these designs to be ready for commercial deployment by the early 2030s; in other words, they would have reached "technical maturity, demonstrated safety and economic benefits, and completed licensing reviews by the US Nuclear Regulatory Commission" (22). Using budget data acquired through the Freedom of Information Act and semistructured interviews with 30 senior nuclear energy experts, we recently analyzed the DOE's efforts to commercialize advanced reactor designs (23,24). NE has spent $2 billion on this effort since the late 1990s, with very little to show for it.…”
Section: Advanced Us Designs Will Not Be Available For Many Decadesmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent analysis of NE's budget expenditures over the past two decades, we found that it lacks both the funding levels and programmatic focus to execute its non-light water reactor mission (Abdulla, et al, 2017). NE's difficulties in fulfilling its role highlight a fundamental challenge to major transitions in the energy system.…”
Section: Introductionmentioning
confidence: 99%